2021
DOI: 10.1136/tsaco-2021-000689
|View full text |Cite
|
Sign up to set email alerts
|

Importance of duration of acute kidney injury after severe trauma: a cohort study

Abstract: BackgroundAcute kidney injury (AKI) is common after severe trauma. AKI incidence and AKI stage have previously been shown to be associated with poor outcomes after trauma. However, AKI duration may also be important for outcomes after trauma, given that it is associated with long-term morbidity and mortality in general intensive care unit (ICU) and hospitalized patients. We hypothesized that duration of AKI is independently associated with poor outcomes after trauma.MethodsA cohort study was conducted at a sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Most of previous studies have confirmed the association between prolonged AKI duration and poorer prognosis in various kinds of patients, including diabetics, those undergoing cardiac surgery, and the critically ill patients. 20 , 24–27 However, another two studies verified that AKI duration was not associated with mortality in critically ill patients. 28 , 29 We considered that the correlation between AKI duration and outcome may be confounded by illness severity, demographic characteristics, underlying diseases, and AKI stage.…”
Section: Discussionmentioning
confidence: 99%
“…Most of previous studies have confirmed the association between prolonged AKI duration and poorer prognosis in various kinds of patients, including diabetics, those undergoing cardiac surgery, and the critically ill patients. 20 , 24–27 However, another two studies verified that AKI duration was not associated with mortality in critically ill patients. 28 , 29 We considered that the correlation between AKI duration and outcome may be confounded by illness severity, demographic characteristics, underlying diseases, and AKI stage.…”
Section: Discussionmentioning
confidence: 99%
“…69% of the AKI group (31% of all patients) had signs of renal dysfunction at admission, but the majority experienced renal recovery within 2 days. 3 The incidence of AKI after surgery ranges from 5% after major abdominal surgeries to nearly 50% after orthotopic liver transplantation. 2 Common causes of AKI in the post-trauma and postsurgical groups include acute tubular necrosis resulting from renal ischemia secondary to hypovolemia, hemorrhage, or shock state, systemic inflammatory response, and nephrotoxic agents including many medications especially antibiotics and non-steroidal anti-inflammatory drugs and myoglobin from rhabdomyolysis.…”
Section: Introductionmentioning
confidence: 99%